2019
DOI: 10.3390/ma12213547
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Cation Species during Sulfate Resistance Tests for Alkali-Activated FA/GGBFS Blended Mortars

Abstract: In this study, the changes in mass, compressive strength, and length of blended mortars were analyzed to investigate their sulfate resistance according to the ground granulated blast furnace slag (GGBFS) blending ratio and type of sulfate solution applied. All alkali-activated mortars showed an excellent sulfate resistance when immersed in a sodium sulfate (Na2SO4) solution. However, when immersed in a magnesium sulfate (MgSO4) solution, different sulfate resistance results were obtained depending on the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…This can be attributed to the low solubility of the resulting magnesium hydroxide, which decreases the pH of the saturated solution, causing the decomposition of CÀ SÀ H gels. [55] Bhutta et al [56] assessed the sulfate resistance of geopolymers prepared from pulverized fuel ash and palm oil fuel ash (POFA) blends. They exposed the prepared samples to 5 % Na 2 SO 4 for a maximum of 18 months to arrive at the results.…”
Section: Durabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…This can be attributed to the low solubility of the resulting magnesium hydroxide, which decreases the pH of the saturated solution, causing the decomposition of CÀ SÀ H gels. [55] Bhutta et al [56] assessed the sulfate resistance of geopolymers prepared from pulverized fuel ash and palm oil fuel ash (POFA) blends. They exposed the prepared samples to 5 % Na 2 SO 4 for a maximum of 18 months to arrive at the results.…”
Section: Durabilitymentioning
confidence: 99%
“…The OPC specimens exhibited a continuous decrease in strength with exposure age, with an ultimate reduction of 63 %. Cho et al [55] studied the effects of different cations (Na + and Mg 2 + ) on fly ash and fly ash/slagblended mortars. The mass and compressive strength of all the samples increased when the samples were exposed to 10 % Na 2 SO 4 for one year.…”
Section: Durabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…It is particularly useful to predict the effects of slag/binder, alkali solution/binder, silicate modulus and the NaOH concentration of the activator. Cho et al [ 12 ] investigated the effect of cations on the sulfate resistance of alkali-activated fly ash and slag blended mortar, concluding that this binder tends to experience deleterious damage when magnesium sulfate solution is used. Kim et al [ 13 ] reported that carbonation leads to a substantial decrease in the abrasion resistance of alkali-activated slag cements.…”
mentioning
confidence: 99%